2022
DOI: 10.1002/jclp.23462
|View full text |Cite
|
Sign up to set email alerts
|

Social difficulties in adolescent attention deficit hyperactivity disorder: Social motivation, social anxiety and symptom severity as contributing factors

Abstract: Background Many interventions have been developed to address the social difficulties commonly experienced by adolescents with attention‐deficit/hyperactivity disorder (ADHD), yet they are largely ineffective. Objective This study examined social impairment among adolescents with and without ADHD, determining whether gender, social anxiety, age, and ADHD symptom type (inattention and hyperactivity/impulsivity) and severity are associated with social impairment. Method Parents and primary caregivers of adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…This may be due to the present study involving samples of Australian respondents collected during the COVID-19 pandemic which was characterised by social distancing and discouraged social interactions, however further research into social motivation following COVID-19 is required to substantiate this claim. Taken together, consistent with previous suggestions ( McKay et al, 2023 ; Smith & Langberg, 2018 ), the present study provides further evidence that social motivation appears to remain stable during childhood, and decline during adolescence for individuals with ADHD.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This may be due to the present study involving samples of Australian respondents collected during the COVID-19 pandemic which was characterised by social distancing and discouraged social interactions, however further research into social motivation following COVID-19 is required to substantiate this claim. Taken together, consistent with previous suggestions ( McKay et al, 2023 ; Smith & Langberg, 2018 ), the present study provides further evidence that social motivation appears to remain stable during childhood, and decline during adolescence for individuals with ADHD.…”
Section: Discussionsupporting
confidence: 92%
“…As hypothesised, adolescents with ADHD had significantly lower levels of social motivation than both their typically developing control counterparts, and children with ADHD. This is consistent with current preliminary literature investigating social motivation in children and adolescents with ADHD, which suggests that social motivation deficits in ADHD do not arise until adolescence ( McKay et al, 2023 ; Smith & Langberg, 2018 ). Furthermore, this study found that typically developing children and adolescents did not significantly differ in their social motivation, whereas adolescents with ADHD had significantly lower levels of social motivation than children with ADHD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further exploration of a diverse range of social cognitions (e.g., biological motion perception) can provide a fresh perspective on the impaired social function observed in ADHD. Moreover, recent studies have indicated that the social cognition in ADHD may vary depending on different factors at the cognitive, pathological, or developmental levels, such as general cognitive impairment 5 , symptoms severity 8 , or age 5 . Nevertheless, understanding how these factors relate to social cognitive dysfunction of in ADHD is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%